When social workers impact policy and don't just implement it : a framework for understanding policy engagement - Gal, John; Weiss, Idit (Research in social work (Policy Press), 2023)
Rather than being seen simply as social policy implementors, in recent decades there has been increasing recognition of social workers as professionals with unique knowledge and insights to contribute to policy formulation and social justice. This book offers a path-breaking, evidence-based theoretical framework for understanding why social workers engage in policy, both as professionals and citizens, and the impact of their actions. Drawing on concepts from social work and the political, sociological and policy sciences, the authors set out the implications of this framework for research, education and practice. Rather than being seen simply as social policy implementors, in recent decades there has been increasing recognition of social workers as professionals with unique knowledge and insights to contribute to policy formulation and social justice. This book offers a path-breaking, evidence-based theoretical framework for understanding why social workers engage in policy, both as professionals and citizens, and the impact of their actions. Drawing on concepts from social work and the political, sociological and policy sciences, the authors set out the implications of this framework for research, education and practice.